Are psychopaths legally insane? - Jefferson, Anneli (Array, 2018)
The question of whether psychopaths are criminally and morally responsible has generated significant controversy in the literature. In this paper, we discuss what relevance a psychopathy diagnosis has for criminal responsibility. It has been argued that figuring out whether psychopathy is a mental illness is of fundamental importance, because it is a precondition for psychopaths’ eligibility to be excused via the legal insanity defense. But even if psychopathy counts as a mental illness, this alone is not sufficient to show the insanity defense is applicable; it must also be shown that, as a result of the illness, specific deficits in moral understanding or control are present. In this paper, we show that a diagnosis of psychopathy will generally not indicate that a defendant is eligible for an insanity defense. This is because the group of individuals subsumed under the diagnosis is so heterogeneous that while some psychopaths do show significant impairments in affect and control which may impact on their responsibility, many psychopaths are not incapacitated in a way relevant to responsibility.